The Compensating Income Variation of Social Capital - Wim Groot; Henriëtte Maassen van den Brink; Bernard M.S. van Praag (Tinbergen Institute, 2007)
There is a small but growing literature on the determinants of social capital. Most of these studies use a measure of trust to define social capital empirically. In this paper we use three different measures of social capital: the size of the individual's social network, the extent of their social safety net and membership of unions or associations. A second contribution to the literature is that we analyze what social capital contributes to our well-being. Based on this, we calculate the compensating income variation of social capital. We find differences in social capital when we differentiate according to individual characteristics such as education, age, place of residence, household composition and health. Household income generally has a statistically significant effect. We find a significant effect of social capital on?life?satisfaction. Consequently, the compensating income variation of social capital is substantial.
Keywords: D1; D6; 330; life satisfaction; social capital; Zufriedenheit; Social Capital; Einkommen